Interfaces entre unidades de conservação e bacias hidrográficas na região de Terra Ronca - Rosa, Lucas Espíndola (2016)
The study area has approximately 6 thousand km2 and is composed of four basins (Água Quente, São Mateus, São Vicente and São Domingos) tributaries of the Paranã River and located in a transition area between the Vão do Paranã (GO) and Oeste Baiano (BA). Among these four basins, (São Mateus and São Vicente) are overlain by two conservation units (Parque Estadual de Terra Ronca and APA Serra Geral de Goiás). The other two basins (Água Quente and São Domingos) are contiguous to the former. The study area contains karstic environments concerning the geological unit of the Bambuí Group, as well as the sandstones of the Urucuia Group, that associated to a polygenic morphosculture and to poorly structured soils make this area naturally vulnerable. In these terms, the research aims to analyze the environmental dynamics between the UC and the hydrographic basins, since the basins inserted in the UC can have their use and dynamically disciplined by the environmental characteristics, while the outer basins do not. The objective is also to understand how the expansion and consolidation of the agricultural frontier in the area of study can be related to the intensification of the vulnerability processes of the study region between 1990 and 2014. It also aims to understand how the variables environmental conditions favor the occupation of the region's lands, as well as understanding soil degradation and alteration mantles (water erosion processes and mass movements). The research uses as theoretical foundation the integrated analysis of the landscape from the interaction between hydrographic basins and UC as units of analysis. The selected method was the multitemporal monitoring of land use and coverage, as well as observation of morphopedological and climatic variables, as well as the empirical analysis of the erosive phenomenon and mass movements, which allowed the distinction of vulnerable sectors to soil loss. Thus, it was verified that the most vulnerable basin is the Água Quente river basin, followed by basin of the São Mateus, São Domingos and São Vicente rivers. It was also observed that the low sectors of these basins are predominantly pasture-occupied, while the high sectors has for predominance the agricultural commodities areas. The most suppressed phytophysiognomies were clean field and dirty field for settlement of agriculture and cerrado ralo for the pastures. The anthropogenic occupation of this region was encouraged by several policies, which contributed to the agricultural activities. In this sense, the UC are important in resources maintaining, since the presented area in 2014 was just over 50% of the remaining vegetation. In addition, the study area is strongly influenced by the morphological conditions, since the remaining vegetation is, predominantly in rocky areas and poorly structured soils. Finally, it can be said that, the collection, treatment and understanding of these different informations was fundamental importance for the evaluation of the synergy between the hydrographic basins and UC in the area of the study.